Participation of the Acehnese Indigenous People in the Formation of Legislation - Kusbari, Gimas (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This journal discusses the participation of the Aceh traditional society in the formation of laws and regulations in Nanggroe Aceh Darussalam. Aceh is a regional government that has a special autonomy related to one of the distinctive characteristics of using Islamic Sharia in forming its policies. Article 96, paragraph 1, of Law Number 13 of 2022 is the legal basis for the public to participate in the formation of statutory regulations. Public participation in the formulation of legislative regulations is the implementation of the objectives of Indonesia for the well-being of the entire Indonesian people. Seeing this, problems arise regarding how to apply Acehnese customary law in regional regulations and the participation of the Acehnese traditional community in the formation of regional regulations. The research method used in this writing is normative juridical, by examining library materials or secondary data. This research explains that the application of customary law in Aceh in regional regulations is called qanun, which is based on Islamic sharia. Then, Ulama and traditional institutions have an important role and certain authority in the formation of laws and regulations.